Low Tidal Volume Ventilation Use in Acute Respiratory Distress Syndrome*. Issue 8 (August 2016) - Weiss, Curtis H.; Baker, David W.; Weiner, Shayna; Bechel, Meagan; Ragland, Margaret; Rademaker, Alfred; Weitner, Bing Bing; Agrawal, Abha; Wunderink, Richard G.; Persell, Stephen D.
Abstract : Objective: Low tidal volume ventilation lowers mortality in the acute respiratory distress syndrome. Previous studies reported poor low tidal volume ventilation implementation. We sought to determine the rate, quality, and predictors of low tidal volume ventilation use. Design: Retrospective cross-sectional study. Setting: One academic and three community hospitals in the Chicago region. Patients: A total of 362 adults meeting the Berlin Definition of acute respiratory distress syndrome consecutively admitted between June and December 2013. Measurements and Main Results: Seventy patients (19.3%) were treated with low tidal volume ventilation (tidal volume < 6.5 mL/kg predicted body weight) at some time during mechanical ventilation. In total, 22.2% of patients requiring an FIO2 greater than 40% and 37.3% of patients with FIO2 greater than 40% and plateau pressure greater than 30 cm H2 O received low tidal volume ventilation. The entire cohort received low tidal volume ventilation 11.4% of the time patients had acute respiratory distress syndrome. Among patients who received low tidal volume ventilation, the mean (SD) percentage of acute respiratory distress syndrome time it was used was 59.1% (38.2%), and 34% waited more than 72 hours prior to low tidal volume ventilation initiation. Women were less likely to receive low tidal volume ventilation, whereas sepsis and FIO2 greater than 40% were associated with increased odds of low tidal volume ventilation use. Four attending physicians (6.2%) initiated low tidal volume ventilation within 1 day of acute respiratory distress syndrome onset for greater than or equal to 50% of their patients, whereas 34 physicians (52.3%) never initiated low tidal volume ventilation within 1 day of acute respiratory distress syndrome onset. In total, 54.4% of patients received a tidal volume less than 8 mL/kg predicted body weight, and the mean tidal volume during the first 72 hours after acute respiratory distress syndrome onset was never less than 8 mL/kg predicted body weight. Conclusions: More than 12 years after publication of the landmark low tidal volume ventilation study, use remains poor. Interventions that improve adoption of low tidal volume ventilation are needed. Abstract : Supplemental Digital Content is available in the text.